Metode Kuis Pilihan yang Paling Mudah dalam Pembelajaran Jarak Jauh bagi Siswa Kelas XII MIPA 4 SMA Negeri 1 Kersana - Rumyati (Cakrawala: Jurnal Pendidikan, 2021)
The objectives of this study are (1) to obtain a description of the effort to measure the level of student absorption through assessment with a kuis learning method that is effective, efficient and easy to implement during the Pandemic through PJJ (Distance Learning), (2) Increase student absorption in the learning process of PPKn subjects through the Kuis learning method in the Pandemic period through PJJ, (3) Solve learning assignment problems through distance learning with the Kuis learning method, (4) Improving student learning outcomes in PPKn subjects through remote learning using the Kuis learning method, (5) Students through the Kuis learning method can find out directly the learning results. This study uses a class action research method that is reflective, so that after implementing a certain action the research will reflect on it with an action as well. From the results of classroom action research shows that the increase in student achievement is the lowest score achieved by students from 30 (UH-1) to 60 (UH-2) and the average score achieved by students from 64.8 (UH-1) to 96.3 UH-2) and the number of students who have not completed has decreased from 5 students at UH-1 to 1 student at UH-2